More Than a Showroom Strategies for Winning Back Online Shoppers - Bachrach, Daniel G.; Ogilvie, Jessica; Rapp, Adam.; Calamusa, Joe.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Showrooming is a growing phenomenon in which customers browse products in a retail store and make purchases of similar products through an online vendor. The authors of this book offer retail managers strategic insight in how to stem the loss of resources to showrooming and transform showrooming customers into in-store sales.
Keywords: Science; Science; Science, general; Electronic books